LEGAL CERTAINTY CHANNELING FUNDS RURAL AGRIBUSINESS ENTERPRISE DEVELOPMENT WITHIN THE FRAMEWORK OF THE DEVELOPMENT OF MICROFINANCE INSTITUTIONS AGRIBUSINESS - Asril Tinambunan; Martin Roestamy (JURNAL ILMIAH LIVING LAW, 2017)
One of the government programs in overcoming the limited access of farmers to capital is through the Rural Agribusiness Development Program (PUAP). However, in the implementation there are irregularities that have impeded of the PUAP Program so as to create legal uncertainty. The purpose of this research is to know the mechanism of distribution, management and development of legal institution of Micro Finance Institution of Agribusiness (MFI-A). The research method used is the sociological juridical approach to find out the mechanism of channeling PUAP funds and the development of MFI-A. This research is also supported by normative approach on the data of legal material in the form of Law Number 19 of 2013 and Act Number 1 of 2013. The mechanism of distributing PUAP funding that is just, effective and targeted is done by selection and verification. Selection is done by selecting Gapoktan to be nominated to receive PUAP. Furthermore, field verification conducted by the District Technical Team. Management of MFI-A as development of Gapoktan saving and loan business unit is done by developing LKM-A product, managing risk, establishing organizational structure and SOP, and using information and computerization system. The form of legal entity in the future for the most suitable MFI-A is a savings and loan cooperative.Keywords: Legal Certainty, PUAP, Gapoktan, and MFI-A